2018
DOI: 10.3892/mmr.2018.8807
|View full text |Cite
|
Sign up to set email alerts
|

lncRNAPCAT29 inhibits pulmonary fibrosis via the TGF‑β1‑regulated RASAL1/ERK1/2 signal pathway

Abstract: Pulmonary fibrosis is a severe respiratory disease characterized by the aggregation of extracellular matrix components and inflammation‑associated injury. Studies have suggested that long non‑coding RNAs (lncRNA) may serve a role in the pathophysiological processes of pulmonary fibrosis. However, the potential molecular mechanisms involving the lncRNA, prostate cancer‑associated transcript 29 (lncRNAPCAT29) in the progression of pulmonary fibrosis are yet to be determined. In the present study, the role of lnc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…19 lncRNAs are involved in modulating the proliferation and apoptosis of lung tissue cells during the development of lung organs, and play a critical role in the pathologic process of pulmonary fibrosis. 7 20 H19 is found to be upregulated and is related to the regulation of inflammation in lung tissues of BPD mice. 10 In this study, we identified that lncRNA H19 was highly expressed in lung tissues of BPD newborn mice, and downregulated H19 relieved pulmonary injury via the miR-17/STAT3 axis and attenuated p-STAT3-induced inflammatory response in BPD newborn mice.…”
Section: Discussionmentioning
confidence: 98%
“…19 lncRNAs are involved in modulating the proliferation and apoptosis of lung tissue cells during the development of lung organs, and play a critical role in the pathologic process of pulmonary fibrosis. 7 20 H19 is found to be upregulated and is related to the regulation of inflammation in lung tissues of BPD mice. 10 In this study, we identified that lncRNA H19 was highly expressed in lung tissues of BPD newborn mice, and downregulated H19 relieved pulmonary injury via the miR-17/STAT3 axis and attenuated p-STAT3-induced inflammatory response in BPD newborn mice.…”
Section: Discussionmentioning
confidence: 98%
“…PKC, served as the hub of multiple intracellular signal pathways, is involved in the construction of key intracellular information network and regulates a variety of in-vivo physiological and pathological processes. PKC can activate the TGF-β1 which is one of the key cytokines involved in the pathogenesis [8], and some studies also reported that ERK1/2 can interact with the TGF-β1 to be involved in the fibrosis [9, 10, 11]. Thus, it can be inferred that PKC-ERK1/2MAPK may participate in the myocardial fibrosis pathogenesis in DM, or served as the underlying regulation mechanism, through which H2S can ameliorate the myocardial fibrosis in DM.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that a prerequisite step in myogenic differentiation of SkMSCs is the activation of MyoD [18,22,40,41]. Moreover, TGFβ1 was reported to regulate the ERK signaling pathway involved in in ammation, regeneration and differentiation [42,43]. To further investigate the mechanism underlying the function of the ECM hydrogels aligned with TGFβ1 in terms of the proliferation and differentiation of SkMSCs, the EdU assays demonstrated that TGFβ1 promoted SkMSC proliferation.…”
Section: Discussionmentioning
confidence: 99%